New perspectives under heterogeneity: mechanism of nutrient heterogeneity on Cd-induced hormesis of soil respiration - Gao, Qian; Yang, Jiangshan; Wu, Junyang; Zhu, Yongli; Fan, Diwu; Han, Jiangang (Frontiers in Microbiology, 2025)
Hormesis is a phenomenon in which low doses of toxins stimulate organisms, while high doses have inhibitory effects. Soil heterogeneity nutrient spatial profoundly influences community structure and stress responses by altering the microenvironment around microorganisms. Studies on hormesis in soil ecosystems have made significant progress, but most of them have overlooked the impact of soil nutrient spatial heterogeneity on hormesis. To examine the effects of nutrient spatial heterogeneity on the hormesis of soil ecosystem under cadmium (Cd) stress, we constructed three patches with different spatial nutrient distribution but the same total nutrient content through different spatial discharge patterns. Different levels of Cd stress were applied to the patches, and after incubation, soil respiration rate, content of dissolved organic matter (DOM) and metagenomic characteristics were measured. The results indicated that higher nutrient spatial heterogeneity enhanced the tolerance of soil respiration to Cd stress (the maximum stimulating dose increased from 0.03 to 3.0 mg·kg−1), and simultaneously improved the compensation capacity (Horzone increased from 0.04 to 21.59). The results also revealed that Cd stress had the least impact on soil microbial diversity of the high heterogeneity samples. The content of DOM initially displayed a hormesis-like phenomenon with increasing Cd stress, followed by a linear increase. Notably, the biphasic change trend became more pronounced as the degree of spatial heterogeneity increased (The maximum stimulation rate of DOM content increases from 10.8 to 22.9%). The hormetic response of soil respiration to nutrient spatial heterogeneity offers novel insights for the identification and mitigation of Cd pollution in ecosystems.